Opinion Leaders in Interpersonal Communication and Their Influence on Alcohol Consumption among Students in Government Tertiary Colleges in Kenya - Maina J. Kamau; Hellen Mberia; Idah Gatwiri Muchunku (Britain International for Academic Research (BIAR) Publisher, 2023)
The study aimed at evaluating the influence of opinion leaders in interpersonal communication on alcohol consumption among students in government tertiary colleges in Kenya. The study was anchored on the two-step flow of communication model. The research used the descriptive cross-sectional survey design and utilized both qualitative and quantitative methods to collect data. From the campuses identified, a representative sample from each campus was chosen. A questionnaire was used to obtain qualitative data from sampled students. An interview guide was instrumental in interviewing key informants, while another guide for focus group discussions was used among the students to gather further qualitative data. Quantitative data was analyzed using descriptive statistics (mainly percentages) and inferential statistics (the chi-square goodness of fit test) with the aid of SPSS. The results were presented using tables and bar graphs. The findings revealed that opinion leaders had a significant influence on the alcohol consumption behavior among college students. Opinion leaders such as peers, family members and celebrities influence behavior. This is an indication that through observation and interpersonal communication, the college students are likely to copy what their opinion leaders are doing, including alcohol consumption.